Chromogranin A and neurone‐specific enolase serum levels as predictors of treatment outcome in patients with metastatic castration‐resistant prostate cancer undergoing abiraterone therapy. (27th April 2016) - Heck, Matthias M.; Thaler, Markus A.; Schmid, Sebastian C.; Seitz, Anna‐Katharina; Tauber, Robert; Kübler, Hubert; Maurer, Tobias; Thalgott, Mark; Hatzichristodoulou, Georgios; Höppner, Michael; Nawroth, Roman; Luppa, Peter B.; et al.
Abstract : Objective: To determine the impact of elevated neuroendocrine serum markers on treatment outcome in patients with metastatic castration‐resistant prostate cancer (mCRPC) undergoing treatment with abiraterone in a post‐chemotherapy setting. Patients and Method: Chromogranin A (CGa) and neurone‐specific enolase (NSE) were determined in serum drawn before treatment with abiraterone from 45 patients with mCRPC. Outcome measures were overall survival (OS), prostate‐specific antigen (PSA) response defined by a PSA level decline of ≥50%, PSA progression‐free survival (PSA‐PFS), and clinical or radiographic PFS. Results: The CGa and NSE serum levels did not correlate ( P = 0.6). Patients were stratified in to low‐ (nine patients), intermediate‐ (18) or high‐risk (18) groups according to elevation of none, one, or both neuroendocrine markers, respectively. The risk groups correlated with decreasing median OS (median OS not reached vs 15.3 vs 6.6 months; P < 0.001), decreasing median clinical or radiographic PFS (8.3 vs 4.4 vs 2.7 months; P = 0.001) and decreasing median PSA‐PFS (12.0 vs 3.2 vs 2.7 months; P = 0.012). In multivariate Cox regression analysis the combination of CGa and NSE (≥1 marker positive vs both markers negative) remained significant predictors of OS, clinical or radiographic PFS, and PSA‐PFS. We did not observe a correlation with PSA response (63% vs 35% vs 31%; P = 0.2). Conclusion: Chromogranin A and NSE did not predict PSA response in patients with mCRPC treated with abiraterone. However, we observed a correlation with shorter PSA‐PFS, clinical or radiographic PFS, and OS. This might be due to an elevated risk of developing resistance under abiraterone treatment related to neuroendocrine differentiation.